2019
DOI: 10.2196/12694
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a Novel Smartphone App (CureApp Smoking Cessation) on Nicotine Dependence: Prospective Single-Arm Interventional Pilot Study

Abstract: Background Mobile apps have been considered to provide active and continuous support for smoking cessation. However, it is yet to be known whether a smoking cessation smartphone app improves long-term abstinence rates in nicotine-dependent patients. Objective This study aimed to evaluate the long-term abstinence effect of a novel smartphone app, CureApp Smoking Cessation (CASC), in patients with nicotine dependence. Methods In this prospectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
81
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 46 publications
(81 citation statements)
references
References 27 publications
0
81
0
Order By: Relevance
“…It consists of a CASC smartphone app for patients with nicotine dependence, a web-based patient management PC software for primary physicians, and a mobile exhaled CO checker. In a previous pilot study, we demonstrated that a prototype of the CASC smartphone app used together with a standard smoking cessation program yielded a higher CAR from weeks 9 to 24 compared with data from a Japanese national survey 7,8,21 .…”
Section: Introductionmentioning
confidence: 84%
“…It consists of a CASC smartphone app for patients with nicotine dependence, a web-based patient management PC software for primary physicians, and a mobile exhaled CO checker. In a previous pilot study, we demonstrated that a prototype of the CASC smartphone app used together with a standard smoking cessation program yielded a higher CAR from weeks 9 to 24 compared with data from a Japanese national survey 7,8,21 .…”
Section: Introductionmentioning
confidence: 84%
“…It also provides professional online mentoring and offers nicotine replacement therapy (over-the-counter medical patches) delivered to the patient’s home. The ascure smartphone app was developed based on research with the CureApp Smoking Cessation app [ 10 - 12 ]. App users have access to tailored guidance in a timely fashion through daily use.…”
Section: Introductionmentioning
confidence: 99%
“…The medical theory, the epidemiological data, the psychotherapeutic aspects, and the user's needs were involved in developing theses apps (63,64). The apps permit the patient to keep a diary of the symptoms associated with quitting, the quantification of the achievements the addict accumulates during the therapy and especially after, and the online psychotherapeutic characteristics (65). The interactive nature of these applications showed increased patient compliance after NRT therapy, with potential value for such programs either as complementary or as a sequence in smoking cessation programs (66).…”
Section: Treatment Strategy In Nicotine Addictionmentioning
confidence: 99%